Enhancing Social Capital: The Role of the School Counselor–Principal Alliance in School Counselor Advocacy Activities for Lesbian, Gay, Bisexual, Transgender, and Questioning or Queer Students. Issue 1 (27th October 2022) - Wikoff, Haley D.; Wood, Susannah M.
This study examined how demographic variables and the school counselor–principal alliance influenced school counselors' advocacy for LGBTQ students as measured by the Lesbian, Gay, Bisexual Active Advocacy Scale-Revised (LGBAAS-R). We surveyed 169 practicing school counselors with at least one year of experience in their current building and working with their current principal. Results indicate that the participant's sexual orientation, engagement with professional development, presence of a Gender and Sexuality Alliance (GSA), the state in which they work, perception of a welcoming environment, years worked with the principal, and perception of a collaborative relationship with the principal were significant predictors of advocacy activity. Through advocacy, school counselors can build social capital in LGBTQ students, yet school counselors' own identity and relationships with principals can influence their ability to engage in advocacy. Note: LGBTQ is intended to represent the diverse range of identities of gender and sexual orientation of individuals.